SERANGGA-SERANGGA PADA BERBAGAI JENIS BERAS DI PASAR TRADISIONAL KOTA MANADO1) THE INSECTS IN VARIOUS TYPES OF RICE IN TRADITIONAL MARKETS IN MANADO CITY1) - Joice L.A. Kawulusan; Jusuf Manueke; Moulwy Frits Dien (COCOS, 2016)
ABSTRACT study aims to Determine the type and Insect Populations in a variety of commodity rice in the traditional market in the city of Manado from February to May 2015. The study used survey methods in some traditional markets in the city of Manado. Traditional markets as the sample location is Pinasungkulan market at (karombasan), Bersehati market at Calaca, Paal Dua market, and Bahu market. Sampling was done by "purposive sampling" is to take a sample of rice were allegedly attacked by pests. Samples were observed once a week for 1 month. Things were observed was kind of Pests and Pest Populations.The results Showed that different types of insect pests found in various commodities of rice in the traditional market town of Manado as many as six types consisting of 5 types of order Coleoptera and one type of the order Lepidoptera. The identification results show that the types of insect pests is Sitophillus sp. (Coleoptera; Curculionidae), Oryzaephilus sp. (Coleoptera; Silvanidae) Tribolium sp. (Coleoptera; Tenebrionidae), Ahasverus sp. (Coleoptera; Cucujidae), Cryptolestes sp. (Coleoptera; Cucujidae) and Corcyra sp. (Lepidoptera; Pyralidae). Observation of the insect pest Populations are highest on the type Sitophillus sp. roomates reached an average (10.77 tails) then successively Tribolium sp. (0,67 tail), Oryzaephillus sp. (0,25 tail), Cryptolestes sp. (0,17 tail), Ahasverus sp (0,15 tails) and Corcyra sp. (0,11 tail), whereas the insect pest population Observations on the location of the sample turned out to be the highest found in traditional markets Bersehati market at Calaca2Reached an average of 5.68 tail, then successively Pinasungkulan market at Karombasan 2.90 tails, Bahu market at Bahu 2.37 tails and Paal Dua market at Paal Dua 1.77 tails.Keywords : Rise, Werehouse pests